2000
DOI: 10.1029/2000jd900396
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of the heterogeneous reaction of nitric acid on calcium carbonate particles

Abstract: Abstract. It has been postulated that the reaction of nitric acid with calcium carbonate, namely, CaCO3(s) + 2HNO3(g) -0 Ca(NO3)2(s) + CO2(g) + H20(g), plays an important role in the atmosphere. In this study, transmission FTIR spectroscopy, diffuse reflectance UV-visible spectroscopy, transmission electron microscopy and a Knudsen cell reactor coupled to a quadrupole mass spectrometer have been used to investigate the heterogeneous reactivity of HNO3 on CaCO3 at 295 K as a function of relative humidity. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
179
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(206 citation statements)
references
References 41 publications
23
179
4
Order By: Relevance
“…Observations by Galy-Lacaux and Modi (1998), in the Sahelian region during the wet season have demonstrated that the alkalinity of the dust particles favors the uptake of nitrogen-containing compounds, especially HNO 3 . Laboratory studies of Goodman et al (2000), have confirmed that HNO 3 removal by CaCO 3 particles could be significant in the atmosphere, as has been suggested by Dentener et al (1996), and Tabazedeh et al (1998). The importance of heterogeneous reactions of HNO 3 on mineral dust has been further supported by a combined laboratory and modeling study of Underwood et al (2001), who have shown that under conditions of high mineral-dust loadings and/or smaller size distributions the importance of these reactions is expected to increase.…”
Section: Introductionsupporting
confidence: 58%
“…Observations by Galy-Lacaux and Modi (1998), in the Sahelian region during the wet season have demonstrated that the alkalinity of the dust particles favors the uptake of nitrogen-containing compounds, especially HNO 3 . Laboratory studies of Goodman et al (2000), have confirmed that HNO 3 removal by CaCO 3 particles could be significant in the atmosphere, as has been suggested by Dentener et al (1996), and Tabazedeh et al (1998). The importance of heterogeneous reactions of HNO 3 on mineral dust has been further supported by a combined laboratory and modeling study of Underwood et al (2001), who have shown that under conditions of high mineral-dust loadings and/or smaller size distributions the importance of these reactions is expected to increase.…”
Section: Introductionsupporting
confidence: 58%
“…Uptake of HNO 3 takes place by acidbase titration on surface sites for dry dust, or in solution with adsorbed water (Goodman et al, 2000). Uptake of SO 2 is thought to take place by aqueous-phase oxidation of SO 2− 3 by O 3 (Ullerstam et al, 2002).…”
Section: Acid Gas Uptake On Dustmentioning
confidence: 99%
“…Ca(NO 3 ) 2 is hydrophilic and fine particulate Ca(NO 3 ) 2 can deliquescence above ∼ 10 % relative humidity (Tobo et al, 2010). During the dust storm period, the fast formed Ca(NO 3 ) 2 can form a liquid film on the dust surface, which further promotes formation of nitric acid on the liquid phase by hydrolysis of other nitrogen oxides like N 2 O 5 (He et al, 2012;Pathak et al, 2009) and adsorption of gaseous HNO 3 (Goodman et al, 2000). Such a positive feedback resulted in a significant formation of NO − 3 even in the dry condition of the dust storm period.…”
Section: Difference In Aerosol Acidity Between Xi'an Andmentioning
confidence: 99%